Physiology and hematology of giant anteaters in captivity (Myrmecophaga tridactyla. Linnaeus, 1758), in Colombia (Revista Sistemas de Producción Agroecológicos, 2019)
The present study was conducted with 20 animals in captivity and retrospectively analyzed 120 medical records which contained the initial assessment of the animal and reports of paraclinical tests. The animals were chemically restricted using ketamine (12 mg/kg) + midazolam (0.2 mg/kg) and xylazine (0.1 mg/kg) in combination in the same syringe and applied intramuscularly; physiological constants, temperature using a mercury thermometer, and heart and respiratory frequencies were monitored with a 2M Littmann® stethoscope. The physiological constants, hematology and blood biochemistry were analyzed and compared with the reference values, which constitutes key information for the clinical assessment and health management of this species. Few works of this type are reported in wildlife in Colombia, and this is the first that establishes reference values for constant physiology and hematology in the giant anteater (Myrmecophaga tridactyla). For body temperature, an average of 33.26°C for males and 34.52°C for females was found; regarding the behavior by age, an average of 33,3 °C for neonates (n=17), 34.74°C for juveniles (n=12) and 34.52°C for adults (n=5) were found. The heart rate was 109 beats per minute (bpm) for males and 83.93 bpm for females, showing significant differences (P
Keywords: blood count; wildlife; blood chemistry; clinic